Comparison and risk stratification of patients presenting with syncope in emergency department. (11th May 2021) - Maqsood, H; Younus, S; Qazi, S; Mazhar, S; Ghaffar, U; Basit, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction  : Syncope is the sudden loss of consciousness, associated with an inability to maintain postural tone, with immediate and spontaneous recovery without requiring electrical or chemical cardioversion. It is a common condition associated with frequent hospitalization or visits to the emergency department. It has a prevalence of 40%, considering a lifetime of 70 years and an annual incidence of 6%. The prognosis after syncope ranges from relatively benign for vasovagal to poor for ventricular tachyarrhythmia,  but invariably creates anxiety and potentially life-changing disruption demanding timely resolution Overall, morbidity and mortality in syncope patients are low, but 1-year mortality can reach significantly higher in certain subgroups. Purpose  : To compare the mortality rates in men and women so that management of the disease and comorbidities can be done accordingly. Methods  : Anyone who presented to the ED with transient loss of consciousness (TLOC) between 2015 and 2018 (n = 11, 718) underwent evaluation for syncope. Initial evaluation included history, physical exam, orthostatic blood pressure, heart rate measurement and a 12-lead ECG with or without echocardiogram. All patients were followed up from their initial ED visit until either April 30, 2019, or death, whichever occurred first. Results  : Among the patients who presented to the ED, 1, 011 (8.62%) females and 1, 391 (11.87%) males were admitted to inpatient facilities. The median age of females at the time of diagnosis was 49 years as compared to 54 years for males. Moreover, females had fewer comorbidities (67.9% with Charlson/Deyo comorbidity score of 0) as compared to males (61.8% with Charlson/Deyo comorbidity score of 0). At 30 days, among those admitted, females had a mortality rate of 2.2% vs. 5.1% for males, and among those discharged, females had a mortality rate of 0.1% vs. 0.6% for males (P < .001 for both). At 1 year, among those admitted, females had a mortality rate of 10.9% vs. 15.6% for males, and among those discharged, females had a mortality rate of 1.8% vs. 3.2% for males (P < .001 for both). All data were analyzed on SPSS version 20 and it was found that males had a 1.2 fold greater risk for death at 1 year compared to females. Conclusion  : By comparing the mortality rates of males and females presenting in the emergency department with syncope, we concluded that the mortality rate is higher in males. This finding will help us to manage the high-risk patients of syncope accordingly.